Patient Perception of Being "Completely Better" After Anterior Cruciate Ligament Reconstruction. Issue 5 (April 2022) - Schneider, Matheus B.; Kung, Justin E.; Zhang, Tina; Rocca, Michael S.; Foster, Michael J.; Meredith, Sean J.; Leong, Natalie L.; Packer, Jonathan D.; Henn, R. Frank
Background: Contextualizing patient-reported outcomes (PROs) by defining clinically relevant differences is important. Considering that anterior cruciate ligament reconstruction (ACLR) ideally results in the restoration of normal knee function, an assessment of patients' perception of being "completely better" (CB) may be of particular value. Purpose: The purpose of this study was to assess the prevalence and characteristics of patients who self-report a CB status after ACLR. Additionally, we aimed to determine whether PROs were associated with a CB status after ACLR as well as to determine CB status thresholds for 2-year and change in values. Study Design: Case-control study; Level of evidence, 3. Methods: We retrospectively analyzed data from an orthopaedic registry at a single institution. Patients were administered the Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF), PROMIS Pain Interference (PI), and International Knee Documentation Committee (IKDC) Subjective Knee Form preoperatively and at 2 years after ACLR. Additionally, patients completed a CB anchor question at 2 years after ACLR. Thresholds for 2-year and change in PRO scores associated with achieving a CB status were identified with 90% specificity. Results: Overall, 95 of the 136 patients (69.9%) considered their condition to be CB at 2 years after surgery. The 2-year and change in PROMIS PF, PROMIS PI, and IKDC scores were significantly better in the CB group than in the non-CB group. Thresholds associated with a CB status for 2-year PROMIS PF, PROMIS PI, and IKDC scores were more reliable than those for changes in scores and were ≥63, ≤44, and ≥80, respectively. Thresholds for the change in PROMIS PF, PROMIS PI, and IKDC scores were ≥19, ≤–16, and ≥44, respectively. Conclusion: The majority of patients reported that they were CB at 2 years after ACLR. This study may serve as a reference for orthopaedic surgeons and researchers when considering outcomes after ACLR.